(3ebOeI aj GdcdGe Ydi GdHSedI hGdMeOdI hGdMeO hGdTcQs - (3RcQjG Hf eMeO Hf CMeO Hf RcQjG GdCfUGQj GdSfjcj GdeUQj GdTGaYqj, CHh jMji , J (B926 (3g` s ((3GdbGgQI s)
(3ChdgG (B:s
(3agPg ebOeI Ydi SHjd GdGNJUGQ ai GdcdGe Ydi GdHSedI hGdMeOdI hYdi GdMeO hGdTcQ hGdeOM dZI hYQaG eY HjGf GdfSHI HjfgeG heY PcQ ahGFO egeI s
(3BNQgG (B:s
(3JeJ GdebOeI HMeO Gddgq s
(3Vef eLehY , JQJjHgG (B: 2s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B46 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B182 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B374s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdfMhs